THE EFFECT OF P FERTILIZER APPLICATION ON SOIL PHOSPHATE FORM AND CORN YIELD ON TYPIC PLINTUDULTS AND PLACIC PETRAQUEPTS - KASNO, ANTONIUS; SUBIKSA, I MADE GUSTI; DWININGSIH, SUTISNI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2009)
Phosphorus is one of macro nutrient for crops, but on the acid soils it become a main limiting factor for increasing plant growth and yield. Phosphorus availability and forms in the soil are influenced by the level of soil acidity, Fe and Al oxide content and the kind of P fertilizer added on the soil. The objective of this research is to study the effect of three source of P fertilizer application on weight of dry corn and on forms of phosphorus on the soil. The experiment had been conducted on Typic Plintudults in Jagang, North Lampung and on Placic Petraquepts in Cicadas, Bogor. The treatments consist of three source of P fertilizer i.e.:SP-36, DAP, and TSP, and control treatment (without P). The P fertilizer rate is 40 kg ha-1. The results of the study show that the P fertilizer application can increase the dry corn weight from 2 t ha-1 to 6 t ha-1, Al-P from 13 ppm to 41-48 ppm, Fe-P from 176 ppm to 263-300 ppm, Rs-P from 27 ppm to 64-73 ppm, and Ca-P from 14 ppm to 18-34 ppm. The increasing of dry corn weight is influenced by the increasing of Al-P, Rs-P, and Ca-P content on the soils. The increasing weight of dry corn is most influenced by the increasing of Ca-P. Phosphate fertilizer on the Placic Petraquepts Cicadas, Bogor can?t increase weight of dry corn. SP-36 and DAP fertilizer can increase of Al-P and Rs-P, whereas TSP fertilizer decreases of Rs-P and Ca-P. TSP fertilizer is suitable for annual crops, increasing of Ca-P and yield of corn.